Recent developments and potential advancement in the kinetics of catalytic oxidation of glycerol - Rozaini, Abdullah; Syamima Nasrin, Mohamed Saleh; Kartina, Embong; Ahmad Zuhairi, Abdullah (Taylor & Francis, 2019)
Glycerol oxidation to value-added chemicals primarily lactic acid has received the attention of many researchers. Heterogeneous catalysis offers a greener route, to boost up product selectivity while minimizing the stages needed in separation process and the amount of waste generated. Therefore, lactic acid could be produced at a more reasonable cost. Currently, most lactic acid production is achieved through fermentation technology that requires high cost and it is also time-consuming. Precious or nonprecious metals must contain Lewis and Brønsted acid sites to influence the reaction pathway. This review focuses on the behavior and performance of heterogeneous catalysts with regards to the roles of the active component, support, and reaction conditions on the reaction pathways. This study also reviews the applicable kinetic models together with a few suggestions that could be adopted to perform reaction kinetic study and catalyst deactivation for lactic acid production via oxidation of glycerol.